Análise do perfil de expressão gênica da glândula de peçonha de Bothrops pauloensis (Bothropoides pauloensis) - Rodrigues, Renata Santos (2010)
Bothrops snake venoms are rich sources of peptides and proteins that have important pharmacological actions causing local and systemic effects such as swelling, bleeding and muscle necrosis. Many toxins from the venom of B.pauloensis have been isolated and characterized by classical biochemical methods. Aiming to describe the transcriptional profile of the gland of B. pauloensis and unveil the pharmacological potential of its products at the molecular level a partial cDNA library has generated and the sequences obtained were identified by similarity analysis against existing international databases. The results show that a total of 1152 clones sequenced, 668 correspond to the sequences of quality, with a high prevalence of transcripts that encode toxins when compared with those that code for proteins involved in cellular functions. Among the sequences encoding toxins (41.5%), metalloproteinases (38%) showed a higher frequency, followed by phospholipase A2 (27%), bradykinin potentiators peptides (16.5%) and C-type lectins (8.2%). Other clones are expressed at lower frequency as serineproteinases (5.1%), L-amino acid oxidase (2.7%), nerve growth factors (NGF) (1.0%) and vascular endothelial growth factors (VEGF) (0.3%), hyaluronidase (0.3%). After analysis of sequences in banks, it was found that there was not only the identification of toxins, but also some cellular transcripts, mostly involved in physiological functions of the gland. Most of these transcripts are involved in cellular gene and protein expression, which reflects a highly specialized tissue for the synthesis of toxins. The analysis of the transcriptome of the gland of B. pauloensis allowed the identification of a BP028cluster containing seven sequences of transcripts encoding LAAO. Cloning and amplification of LAAO generated a fragment of 1548 base pairs (bp) encoding a mature protein of 516 amino acid residues with a molecular mass of 58 kDa, pI 6.3 and only one glycosylation site. According to the phylogenetic analysis svLAAOs from Viperidae and Elapidae snake showed clear separation, indicating a significant correlation with speciation, demonstrating that genes corresponding to these sequences are orthologous